The derivative of the natural log function, y = ln(x), is 1/x. This guide will focus on how to use this rule to find derivatives of functions involving the natural log.

derivative-of-lnx

Examples

Remember that when taking the derivative, you can break the derivative up over addition/subtraction, and you can take out constants. This allows us to find the following.

  • \left(3\ln(x)\right)^{\prime} = 3\left(\dfrac{1}{x}\right) = \dfrac{3}{x}
  • \left(\dfrac{\ln(x)}{5}\right)^{\prime} = \dfrac{1}{5}\left(\ln(x)\right)^{\prime} = \left(\dfrac{1}{5}\right)\left(\dfrac{1}{x}\right) = \dfrac{1}{5x}
  • \left(2x^2 - \ln(x)\right)^{\prime} = 4x - \dfrac{1}{x}

Using the laws of logarithms

For some derivatives involving ln(x), you will find that the laws of logarithms are helpful. In terms of ln(x), these state:

properties-of-ln

Using these, you can expand an expression before trying to find the derivative, as you can see in the next few examples.

Example

Find the derivative of the function.
y = \ln(x^2)

Before applying any calculus rules, first expand the expression using the laws of logarithms. Here, we can use rule (1). This step is all algebra; no calculus is done until after we expand the expression.

y = \ln(x^2) = 2\ln(x)

Now, take the derivative. This is the calculus step.

y^{\prime} = \left(2\ln(x)\right)^{\prime}

= 2\left(\ln(x)\right)^{\prime}

= 2\left(\dfrac{1}{x}\right)

= \boxed{\dfrac{2}{x}}

In the example above, only one rule was needed to fully expand the expression. The next example shows you how to apply more than one rule.

Example

Find the derivative of the function.
y = \ln(5x^4)

Before taking the derivative, we will expand this expression. Since the exponent is only on the x, we will need to first break this up as a product, using rule (2) above. Then, we can apply rule (1).

y = \ln(5x^4) = \ln(5) + \ln(x^4) = \ln(5) + 4\ln(x)

Now take the derivative of the expanded form of the function.

y^{\prime} =  \left(\ln(5) + 4\ln(x)\right)^{\prime}

=  \left(\ln(5)\right)^{\prime} + 4\left(\ln(x)\right)^{\prime}

=  4\left(\dfrac{1}{x}\right)

=  \boxed{\dfrac{4}{x}}

You may be wondering what happened to ln(5). Remember – this is a constant. The derivative of a constant is zero.

None of these examples have used rule (3), so let’s look at one more example to see how that might be applied.

Example

Find the derivative of the function.
y = \ln\left(\dfrac{6}{x^2}\right)

Here we have a fraction, which we can expand with rule (3), and then a power, which we can expand with rule (1). Remember that this is just algebra – no calculus is involved just yet.

y = \ln\left(\dfrac{6}{x^2}\right) = \ln(6) - \ln(x^2) = \ln(6) - 2\ln(x)

Now that we have ln(x) by itself, we can apply the derivative rule for the natural log.

y^{\prime} =  \left(\ln(6) - 2\ln(x)\right)^{\prime}

=  \left(\ln(6)\right)^{\prime} - 2\left(\ln(x)\right)^{\prime}

=  -2\left(\dfrac{1}{x}\right)

=  \boxed{-\dfrac{2}{x}}

As in the previous example, ln(6) is a constant, so its derivative is zero.

Combining with other rules

Each of the derivatives above could also have been found using the chain rule. As you study calculus, you will find that many problems have multiple possible approaches. However, there are some cases where you have no choice. For example, consider the following function.

y = \ln(3x^2 + 5)

Since this is not simply ln(x), we cannot apply the basic rule for the derivative of the natural log. Also, since there is no rule about breaking up a logarithm over addition (you can’t just break this into two parts), we can’t expand the expression like we did above. Instead, here, you MUST use the chain rule.

Summary

Remember the following points when finding the derivative of ln(x):

  • The derivative of ln(x) is 1/x.
  • In certain situations, you can apply the laws of logarithms to the function first, and then take the derivative.
  • Values like ln(5) and ln(2) are constants; their derivatives are zero.
  • ln(x + y) DOES NOT EQUAL ln(x) + ln(y); for a function with addition inside the natural log, you need the chain rule.
  • ln(x – y) DOES NOT EQUAL ln(x) – ln(y); for a function with subtraction inside the natural log, you need the chain rule.

Continue your study of derivatives

Keep up to date with MathBootCamps!
Subscribe